PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA MIO M3 CW PADA PT. HASJRAT ABADI Outlet PUUWATU - Ningsi, Ahyan Septiyani; utha, arifin; BB, suryani (Business UHO: Jurnal Administrasi Bisnis, 2016)
This study aims to examine how much influence Brand Image and Price have on products so that companies can know consumers in making purchasing decisions Independent variables consist of Brand Image (X1) and Price (X2) The dependent variable is the Purchasing Decision (Y) of Yamaha Mio M3 Cw at PT Hasjrat Abadi Outlet Puuwatu Sample of 56 respondents taken using the Total technique Sampling The analysis used is multiple regression analysis, the result is, Y = 0.383X1 + 0.601X2 The most independent variable influencing the dependent variable is the brand image variable (0.383) and followed by the price variable (0.601). of 0.867 or 86.7 percent means that the coefficient of determination model is good.This study was conducted with m questionnaire distributed to several consumers of Yamaha Mio M3 Cw in total sampling and analyzed with multiple linear regression. This model emphasizes the influence of Brand Image and Price on Purchasing Decisions that the results of the analysis are processed using SPSS 16. The results show that there are two hypotheses that have been tested in this study, namely Brand Image and Price. Where the two hypotheses have a significant positive effect on purchasing decisions for Yamaha Mio M3 Cw, especially in Kendari City. The results showed that the research model was acceptable.Â